RELATIONSHIP BETWEEN CONVERGENT-DIVERGENT THINKING CHARACTERS AND MIND MAP - - Junaidi (JAFFA, 2017)
This study aims to evaluate the mind mapping material in creativity course syllabus. The test is performed to see the students' convergent-divergent thinking characters. The treatment of the accounting mind map using numerical symbols was given to students before and after the thinking character tests. The test used paired sample t-test, Wilcoxon, and Chi-Square. The test result proves that there is an increase of students' divergent thinking character after given the material of accounting mind map using numerical symbols compared to before treatment. However, there is no difference of convergent thinking characters in class C before and after treatment.